Emerging mental health challenges, strategies, and opportunities in the context of the COVID-19 pandemic: Perspectives from South American decision-makers - Daniel A. Antiporta; Andrea Bruni (Pan American Health Organization, 2020)
Objective. To identify emerging mental health problems, strategies to address them, and opportunities to reform mental health systems during the COVID-19 pandemic in South America. Methods. An online questionnaire was sent to mental health decision-makers of ministries of health in 10 South American countries in mid-April 2020. The semi-structured questionnaire had 12 questions clustered into three main sections: emerging challenges in mental health, current and potential strategies to face the pandemic, and key elements for mental health reform. We identified keywords and themes for each section through summative content analysis. Results. Increasing mental health burden and needs were reported as direct and indirect consequences of the COVID-19 pandemic. National lockdowns challenge the delivery and access to mental health treatment and care. Strategies to meet mental health needs rely heavily on timely and adequate responses by strengthened mental health governance and systems, availability of services, virtual platforms, and appropriate capacity-building for service providers. Short- and medium-term strategies focused on bolstering community-based mental health networks and telemedicine for high-risk populations. Opportunities for long-term mental health reform entail strengthening legal frameworks, redistribution of financial resources, and collaboration with local and international partners. Conclusions. Mental health and psychosocial support have been identified as a priority area by South American countries in the COVID-19 response. The pandemic has generated specific needs that require appropriate actions, including implementing virtual interventions, orienting capacity-building toward protecting users and health providers, strengthening evidence-driven decision-making, and integrating mental health and psychosocial support in high-level mechanisms guiding the response to COVID-19.